The “Bando Borghi” and the Regeneration of Villages in the Province of Foggia - Fanizza, Fiammetta; Spallone, Fiorella (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2024)
Based on the expected results of the "Bando Borghi" (call PNRR of 2022) this article deals with the regeneration strategies of the Italian villages. In particular, the article discus about how and how much the extent cultural valorization, the rediscovery of local identities and the slow tourism trends can contribute both to the revitalizing and the repopulating the over five thousand villages spread all over the Italian territory. The article argues on innovative aims of some case studies of the Province of Foggia: Chieuti, Rignano Garganico, Serracapriola and Zapponeta. In particular, it focuses on methods and multidisciplinary approaches and discuss the impact of these latter to perform planning process in reference with cultural and social regeneration goals. All the projects presented consider the valorization of the villages as a dimension capable of relating to the collective identity and, finally, in each of the four small villages in province of Foggia involved in Bando Borghi the final goal is the attempt to increase of levels of resilience through the promotion of a diversified use of the natural and cultural heritage. Remarkable the strong collaboration in planning activities between University of Foggia (Sociological team in partnership with the Atheneum Grant Office) and INU, National Institute of Urban Planning, Apulia Section. This collaboration empathizes the strength of identity into design work and define a new way to elaborate proposal to develop with participative process. This collaboration can be assumed as an interesting test both for the enlargement of public discourse and for awareness citizenships.in